Actualizing Gadow's moral framework for nursing through research - Minicucci, Daryl Sharp (Nursing philosophy, 2003)
The purpose of this paper is to describe how Sally Gadow's perspectives on existential advocacy as the moral framework for the nurse-patient relationship were synthesized with a general theory of motivation, self-determination theory (SDT), to inform the design of a study in which the influence of interpersonal care on the process of tobacco dependence treatment was explored. Consistent with the tenets of existential advocacy, participants who perceived their care providers as interpersonally sensitive and bringing more of their whole selves to the care encounter reported more autonomous motivation and felt competence for stopping smoking. The integration of existential advocacy with SDT, which led to the empirical work in which Gadow's ideas were actualized and her model supported, is described. Study findings are discussed in light of Gadow's philosophical views, and implications for nursing highlighted.